VILLAGE FUND MANAGEMENT ACCORDING TO SAPPURISDHAMMA OF BANSONG SUBDISTRICT MUNICIPALITY, WIANGSA DISTRICT, SURAT THANI PROVINCE - Na-Sen, Wiriya; Suvadฺdฺho (Sookpanich) Phrakrupalad Athit (Journal of MCU Nakhondhat, 2024)
The purpose of this research article is to study 1) Village fund management according to Sappurisadham principles and 2) Guidelines For village fund management according to Sappurisadham principles of Ban Song Subdistrict Municipality. Wiang Sa District Surat Thani Province It is mixed methods research. The sample group consisted of 367 members of the Ban Song Subdistrict Municipality Village Fund, 5 key informants/person, and a purposive sample was selected. The research tools used were questionnaires and in-depth interviews. Data were analyzed using frequency, percentage, mean, and standard deviation. and content analysis. The research results found that: 1) Village fund management according to Sappurisadham principles of Ban Song Subdistrict Municipality. Overall, every aspect was at a high level, average ( = 4.19). The aspect with the highest average was Atthannuta (knowledge of meaning or knowledge of results) average value ( = 4.30), followed by Dhammannuta (knowledge of Dhamma or knowledge of causes) average value ( = 4.20) and the Dhamma principle with the lowest average value is the Pukkalaparopranyuta principle. (Knowledge of people) Average ( = 4.14) and 2) Guidelines for promoting village fund management according to the principles of Sappurisadham of Ban Song Subdistrict Municipality 1) The committee should review knowledge and understanding about Village fund management on a regular basis. 2) There is planning and analysis of external situations that may affect village fund management. 3) There should be an assessment of the capacity of the committee and members, and 4) Participation in participation should be promoted. Village fund management from all sectors